Filming fiction : Tagore, Premchand, and Ray - Asaduddin, M. (Mohammad), 1958-; Ghosh, Anuradha (New Delhi : Oxford University Press, 2012)
Papers presented at a seminar on Fiction into film : Satyajit Ray's interpretation of Tagore and Premchand, held at Jamia Millia Islamia during 23-25 November 2006.
Includes bibliographical references.
Keywords: Ray, Satyajit, -- 1921-1992 -- Criticism and interpretation -- Congresses; Tagore, Rabindranath, -- 1861-1941 -- Film and video adaptations -- Congresses; Premacanda, -- 1881-1936 -- Film and video adaptations -- Congresses; Women in literature -- Congresses; Women in motion pictures -- Congresses; Indic literature -- Film and video adaptations -- Congresses; Chess in literature -- Congresses